Perception of Job Stress and Its Impact on The Job Performance of IT Company Employees in Chennai City - Malathi , Dr.T.; Srilatha , B. Venkata (International Journal of Accounting and Economics Studies, 2025)
Job performance means the ability of an individual to complete their assigned work using available resources effectively. Although extensive research has been conducted on occupational stress and job performance worldwide, India has not focused on this area. In recent years, there has been a notable increase in the prevalence of stress inside organisations. Hence, this study was thought of examining the stress of the job and its impact on employee performance in selected IT Companies in Chennai city. A sample of 121 IT Company employees was taken for this study by using non-probability sampling methods. Job stress factors such as workload and pressure, roles and responsibilities, relationships and communication, and personal factors were analysed to assess the level of job stress and its impact on job performance. The results of this study revealed that workload and work pressure and relationships, and communication factors did impact employee performance in IT companies in Chennai City.